GAMIFICACION Y SU INFLUENCIA EN EL APRENDIZAJE DE LOS ESTUDIANTES DE BACHILLERATO EN INFORMÁTICA DE LA UNIDAD EDUCATIVA DIEZ DE AGOSTO, PERIODO ACADÉMICO OCTUBRE 2023 –MARZO 2024. - SOLÓRZANO UBILLA ROMINA JAILIN. (2024)
The central theme of this research is: Gamification and its influence on the learning of high school students in computer science at the Diez de Agosto Educational Unit, academic period October 2023 - March 2024. The objective was to determine how gamification influences the learning of third-year Computer Science high school students. The methodology is supported by the quantitative research model, because through this method information is collected through a survey directed at the students of the Diez de Agosto Educational Unit in the third year of the Computer Science baccalaureate, through a questionnaire of questions, international, national and local level; exploratory, because for the collection of information, a one-time survey was used in which third-year high school students in the area of computer science participated; descriptive, because the knowledge about the variables gamification, learning and the population investigated were one hundred and twenty third-year high school students. The conclusions reached were: that the use of gamification contributes to the learning of third-year Computer Science Baccalaureate students. The results of this work were that 75.3% of the third-year computer science high school students indicated that they agree that gamification is an innovation technique in educational settings while 24.70% of those surveyed selected that they are I totally agree with what was described above.